Definitive chemoradiotherapy combined with anti-PD-1 immunotherapy for inoperable esophageal squamous cell carcinoma: a multicenter real-world study - Xiongtao Yang; Xiaomin Wang; Qin Xiao; Xiaolin Ge; Nuo Yu; Jiao Li; Guojie Feng; Ziyu Zheng; Yingying Jiang; Lin Lu; Xiaojie Xia; Lei Deng; et al. (Cancer Biology & Therapy)
The potential benefits of adding immune checkpoint inhibitors (ICIs) to definitive chemoradiotherapy (dCRT) for inoperable esophageal squamous cell carcinoma (ESCC) remain unclear, different timing for immunotherapy intervention during the peri-dCRT period on survival outcomes is worth exploring. Patients with inoperable ESCC receiving dCRT combined with ICIs between April 2018 and April 2022 were recruited from five hospitals in China. A historical control group treated with dCRT alone was used for comparison. Stabilized inverse probability of treatment weights (sIPTW) analyses were conducted to compare survival. The survival outcomes and treatment-related adverse effects were analyzed. A total of 290 patients with inoperable ESCC who received dCRT+ICI treatment were analyzed. The median follow-up was 35.7 months. The 1-year and 2-year overall survival (OS) rates were 86.7% and 66.9%, respectively, and the 1-year and 2-year progression-free survival (PFS) rates were 66.7% and 47.3%, respectively. The median PFS was 22.4 months, and the median OS was not reached. The dCRT+ICI group had significantly longer OS than the historical control group (2-year OS: 66.9% vs. 56.5%, for sIPTW-adjusted data: HR = 0.62, p < .001). After sIPTW, no differences in OS were found among the induction, concurrent, and consolidation groups. The sIPTW-adjusted analysis showed that both the induction and concurrent groups had significantly longer PFS than the consolidation group. Combining immunotherapy with dCRT improved survival outcomes and demonstrated a favorable safety profile in patients with inoperable ESCC. Induction or concurrent immunotherapy may provide superior survival benefits compared to consolidation immunotherapy.Trial registration Trial no. NCT04821778 registered in ClinicalTrials.gov